The Psychology of Technology-Human Resource Interactions: Balancing Automation and Human Connection in the Digital Workplace - Khan, Zafar; Niaz, Falak; Sultan, Farukh; Saeed, Ozal (Advances in Psychological Sciences and Applications, 2025)
In the evolving digital workplace, technology and Human Resource Management (HRM) have become increasingly intertwined, redefining traditional HR functions and relationships. This paper explores the psychological dynamics and organizational implications of integrating advanced technologies such as Artificial Intelligence (AI), machine learning, and analytics into HRM. Drawing from over 25 scholarly references, the study analyzes how technology influences recruitment, onboarding, performance evaluation, and employee development. The findings emphasize that while digital tools enhance efficiency, human-centric approaches remain indispensable in fostering engagement, motivation, and well-being. The study highlights the importance of a balanced HRM strategy that harmonizes technological efficiency with psychological and emotional human needs. The paper concludes that sustainable HRM in the digital era must be anchored in empathy, ethical judgment, and continuous learning.